Diabetes Mellitus and its impact on patient-profile and in-hospital outcomes in peripheral artery disease - Keller, Karsten; Schmitt, Volker H.; Vosseler, Markus; Brochhausen, Christoph; Münzel, Thomas; Hobohm, Lukas; Espinola-Klein, Christine (Journal of Clinical Medicine, 2021)
Background: In patients with peripheral artery disease (PAD), the impact of diabetes mellitus (DM) on patient-profile and adverse in-hospital events is not well investigated. Methods: The German nationwide inpatient sample 2005-2019 was used for this analysis. Hospitalized PAD patients were stratified for DM and the influence of DM on patient-profile and adverse in-hospital events was investigated. Results: Our study comprised 2,654,871 hospitalizations (54.3% aged ≥70 years, 36.7% females) of patients with PAD in Germany 2005-2019. Among these, 864,691 (32.6%) patients had DM and 76,716 (2.9%) died during hospitalization. Diabetic PAD patients revealed an aggravated cardiovascular profile (Charlson Comorbidity Index: 6.0 (5.0-8.0) vs. 4.0 (3.0-5.0), p < 0.001). PAD patients with DM showed a higher rate of in-hospital mortality (3.5% vs. 2.6%, p < 0.001), as well as major adverse cardiovascular and cerebrovascular events (MACCE, 4.7% vs. 3.3%, p < 0.001) and had more often operated with amputation surgery (16.4% vs. 9.1%, p < 0.001). DM was an independent predictor of in-hospital mortality (OR 1.077 (95%CI 1.060-1.093), p < 0.001) and MACCE (OR 1.118 (95%CI 1.103-1.133), p < 0.001). In addition, amputations were also associated with DM (OR 1.804 (95%CI 1.790-1.818)), p < 0.001). Conclusions: DM is associated with an unfavorable clinical patient-profile and higher risk for adverse events in PAD patients, including substantially increased in-hospital mortality as well as MACCE rate, and were more often associated with amputation surgeries.
Gesehen am 05.01.2022